Application of Quizizz Educational Games and Rewards to Increase Students' Learning Motivation - Efy Lilawati; Esti Untari; Sri Kustiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Learning through online that does not do face-to-face certainly has various challenges. One of the challenges is the lack of student learning motivation. Efforts to create an interesting and fun learning atmosphere require several breakthroughs, both in curriculum development, learning media innovation and fulfilling educational infrastructure. This study aims to describe the application of the quizizz educational game and the provision of rewards to increase the learning motivation of fifth grade students at SDN Tarokan 5 Kediri. The approach used in this research is a qualitative approach with the type of classroom action research. The research was carried out in two cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The subjects of the research were the fifth grade students of SDN Tarokan 5, totaling 10 students consisting of 6 boys and 4 girls. The data in this study are the results of observations of teacher activities, student activities, and student learning motivation. Data collection techniques used by using observation, questionnaires, field notes and documentation. The results of the study by applying the quizizz educational game and giving rewards can run well and have increased. In the first cycle the average value of teacher activity was 98% in the very good category, increasing to 100% with the very good category in the second cycle. The value of student activity is 83.5% in the good category, in the second cycle it increases to 91.5% in the very good category. Meanwhile, the result of students' learning motivation in the pre-action was 53% with a very low category. In the first cycle, the results of the observation of students' learning motivation increased to 77% in the high category. Furthermore, in the second cycle, the results of the observation of students' learning motivation increased to 82% with a very high category. The conclusion of this study is that the application of the quizizz educational game and the giving of rewards to the fifth grade students of SDN Tarokan 5 Kediri, has been carried out by the teacher and students very well.